2014
DOI: 10.1016/j.biochi.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Novel antibacterial peptides from the skin secretion of the Indian bicoloured frog Clinotarsus curtipes

Abstract: HPLC elution profile and MALDI TOF MS analysis of electro-stimulated skin secretion of the Indian Ranid frog Clinotarsus curtipes of the Western Ghats confirmed the presence of multiple peptides. Peptides eluted out of the C18 column at higher hydrophobic solvent region showed antibacterial activity against diverse bacterial strains, including the clinical isolates of V. cholerae and methicillin resistant Staphylococcus aureus (MRSA). Peptidomic analysis of the most potent chromatographic effluent fraction ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Most of the studies dealing with toad parotoid gland and skin secretions focus on the biological activities of biogenic amines, alkaloids, and peptides. Therefore, these molecules and their pharmacological and toxic effects are well characterized (Abraham et al., ). However, there is limited information regarding the content and identification of proteins from toad parotoid glands, as well as their pharmacological and toxic properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies dealing with toad parotoid gland and skin secretions focus on the biological activities of biogenic amines, alkaloids, and peptides. Therefore, these molecules and their pharmacological and toxic effects are well characterized (Abraham et al., ). However, there is limited information regarding the content and identification of proteins from toad parotoid glands, as well as their pharmacological and toxic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Although parotoid secretions are commonly reported as sources of toxic compounds, some studies have reported the presence of molecules having pharmacological activities. The action against cardiovascular disorders, cancer, microbial infections, diabetes, and inflammation are examples of activities related to biogenic amines, cardiotonic steroids, and alkaloids (Meng et al., ; Abraham et al., ). However, information on purification, biochemical characterization, and biological activities of proteins and peptides from these glands is very limited in the literature.…”
mentioning
confidence: 99%
“…subtilis, E. coli, Proteus vulgaris, Sarcina lutea, Enterobacter aerogenes, Salmonella typhimurium and S. aureus. Similarly, Abraham et al (2014) found that electrically stimulated skin secretion of the Indian Ranid frog Clinotarsus curtipes of the Western Ghats, Kerala, India contains multiple peptides having antibacterial activity against diverse bacterial strains, including V. cholerae and Methicillin Resistant S. Aureus (MRSA). Dorsal skin secretions of Iranian frog, Rana ridibanda, was also shown to have a significant antibacterial activity against MRSA (Abbasi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…2a, e). The immune modulatory properties of AMPs include modulating pro- and anti-inflammatory responses through [41] various signaling pathways [40] directly [42] or indirectly [43] recruiting effector cells including phagocytes to the site of infection, enhancing intracellular [44] and extracellular [45] bactericidal activity. AMPs also mediate macrophage differentiation [46] which is required for effective clearance of pathogens from the host.…”
Section: Discussionmentioning
confidence: 99%